COVID-19 Challenges and Human Resource Management in Organized Retail Operations. / Desafíos del Covid-19 y la administración de recursos humanos en operaciones minoristas organizadas. - ALI SULAIMAN, MOHAMMED ALI BAIT; AHMED, MOHAMMED NAZEER; SHABBIR, MUHAMMAD SALMAN (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study emphasizes on identifying and overcoming Covid-19 challenges, faced by human resource management (HRM) while managing personnel in organized retail stores. Data for this study were drawn from a review of secondary sources on practical insights about Covid-19 challenges, suggesting tangible solutions to solve them, which should be addressed at the earliest to ensure successful retail operations avoiding unexpected chaos created by the Covid-19 pandemic. RESUMEN El estudio enfatiza en identificar y superar los desafíos de Covid-19, que enfrenta la administración de recursos humanos (ARH) mientras administra el personal en las tiendas minoristas organizadas. Los datos para este estudio se obtuvieron de una revisión de fuentes secundarias en conocimientos prácticos sobre los desafíos de Covid-19, sugiriendo soluciones tangibles para resolverlos, lo cual debe abordarse lo antes posible para garantizar operaciones minoristas exitosas y evitar el caos inesperado creado por la pandemia Covid-19.